2017
DOI: 10.1097/md.0000000000008778
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy with gallbladder bed cautery might be sufficient for T1bN0M0 neuroendocrine carcinoma of gallbladders

Abstract: Introduction:Neuroendocrine carcinoma was a rare kind tumor in gallbladders. So far, there is no consensus of treatment of the gallbladder neuroendocrine carcinoma.Case presentation:Three patients, 1 male and 2 females, were admitted in our hospital because of right upper quadrant pain. No one complained fever, jaundice, weight loss, or carcinoid syndrome-related symptoms such as diarrhea, flushing, edema, and wheezing. The MRI detected the broad base of gallbladder tumors. However, they refused any radical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, the presence of lymph node metastasis around the gallbladder and retroperitoneum is difficult to distinguish from the other gallbladder tumors (30). Imaging examinations provide significant results only when used at an early stage and then provide aid in establishing a treatment plan (31).…”
Section: Diagnosismentioning
confidence: 99%
“…However, the presence of lymph node metastasis around the gallbladder and retroperitoneum is difficult to distinguish from the other gallbladder tumors (30). Imaging examinations provide significant results only when used at an early stage and then provide aid in establishing a treatment plan (31).…”
Section: Diagnosismentioning
confidence: 99%
“…Compared with conventional laparotomy, our department found that laparoscopic surgery for gallbladder carcinomas may provide comparable perioperative outcomes and it is helpful for less intraoperative bleeding, shorter postoperative days of oral diet recovery and hospital stays [6]. In the study performed by Liu et al, all three patients with GB-NEC at T1bN0M0 stage underwent laparoscopic cholecystectomy with gallbladder bed cautery, and no recurrences were found during the at least 26.0 months' follow-up without any postoperative chemotherapy or radiotherapy (Table 3) [7]. However, there are few reports discussing laparoscopic surgery for GB-NECs at advanced stages.…”
Section: Discussionmentioning
confidence: 96%
“…[ 21 ] It has been reported that simple cholecystectomy is enough for in situ GB-NENs and those of T1N0M0 stage. [ 4 ] In the study performed by Liu et al, [ 22 ] all 3 GB-NEC patients who were in T1bN0M0 stage underwent laparoscopic cholecystectomy with gallbladder bed cautery, and no recurrences were found without any chemotherapy or radiotherapy during the follow-up period of at least 26 months. For those who are diagnosed at more advanced stage without distant metastasis, radical cholecystectomy is the preferred treatment if it is available.…”
Section: Discussionmentioning
confidence: 99%